Fabrication of three-dimensional plasmonic cavity by femtosecond laser-induced forward transfer - Chen, Wei Ting (2013)
We fabricated a three-dimensional five-layered plasmonic resonant cavity by low-cost, efficient and high-throughput femtosecond laser-induced forward transfer (fs-LIFT) technique. The fabricated cavity was characterized by optical measurements, showing two different cavity modes within the measured wavelength region which is in good agreement with numerical simulations. The mode volume corresponding to each resonance is found to be squeezed over 10^4 smaller than the cube of incident wavelength. This property may facilitate many applications in integrated optics, optical nonlinearities, and luminescence enhancement, etc.